Europe in Revolt - Príncipe, Catarina; Sunkara, Bhaskar (Haymarket Books, 2016)
"The global recession has had political consequences across the world, but nowhere greater than in the periphery of Europe. In response, a massive wave of resistance erupted across the continent. The book examines the key parties and figures behind this insurgency, with insider coverage of both the roots of the social crisis and the radicals seeking to reverse it. Catarina Príncipe is a social movement activist from Portugal and a contributing editor at Jacobin magazine. Bhaskar Sunkara is the founding editor and publisher of Jacobin magazine"--Provided by publisher.